Population Dynamics of Escherichia coli Growing under Chemically Defined Media - Honoka Aida; Bei-Wen Ying (Scientific Data)
Abstract Bacterial population dynamics are essential for understanding microbial survival strategies and optimizing cell culture systems. However, the variation in these dynamics across different environmental conditions remains largely unexplored. This study presents a comprehensive dataset of Escherichia coli growth under well-defined laboratory conditions, comprising 13,608 growth curves across 1,029 chemically defined media made from 44 pure compounds. Growth was monitored in 96-well microplates, capturing temporal changes in optical density linked to specific medium compositions. This dataset bridges environmental inputs with population-level responses, offering a rich resource for systems biology. By providing high-resolution data on bacterial growth behavior, it supports the discovery of fundamental principles governing cellular adaptation and dynamics.